What is equivalent to this formula: y=3(x+5)(x-2)

Question

What is equivalent to this formula: y=3(x+5)(x-2)

in progress 0
Emery 4 weeks 2022-01-02T20:21:21+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-01-02T20:22:47+00:00

    Answer:

    y = 3*(x^2) + 9x -30

    Step-by-step explanation:

    y=3(x+5)(x-2)

    y = (3*x + 3*5) * (x – 2)

    y = (3*x + 15) * (x – 2)

    y = 3*x*x + 3*x*(-2) + 15*x + 15*(-2)

    y = 3*(x^2) – 6x + 15x – 30

    y = 3*(x^2) + 9x -30

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )